Magnetic Characteristics Measurements in HTc Superconductors (Global Journal of Science Frontier Research, 2012)
Selected methods for measurements magnetic quantities in HTc superconductors are discussed. First one is based on an analysis of the magnetic hysteresis curves, while second follows from the investigations of the dynamic anomalies of the current-voltage characteristics in slowly varying magnetic field.